Armezon Pro, Status, Verdict, Glyphosate, Zidua, and Atrazine for Sequential Weed Control in Glyphosate-Resistant Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several herbicide treatments applied sequentially in irrigated corn. Kochia control was 95% or more with all treatments at 1 day after late postemergence application (1 DALP) and 100% regardless of treatment at 63 days after late postemergence application (63 DALP). Palmer amaranth and green foxtail control was 98 to 100% and 83 to 93%, respectively, with all preemergence treatments at 1 DALP. A second late postemergence application was needed to achieve 100% control of Palmer amaranth and green foxtail 63 DALP. The single early postemergence treatment controlled Palmer amaranth and green foxtail 90 and 91% at 63 DALP.
Keywords: Early postemergence; residual control